De‐palmitoylation by N‐(tert‐Butyl) hydroxylamine inhibits AMPAR‐mediated synaptic transmission via affecting receptor distribution in postsynaptic densities. (17th June 2018) - Xia, Zhi‐Xuan; Shen, Zu‐Cheng; Zhang, Shao‐Qi; Wang, Ji; Nie, Tai‐Lei; Deng, Qiao; Chen, Jian‐Guo; Wang, Fang; Wu, Peng‐Fei
Summary: Aims: Palmitoylation of α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid receptors (AMPARs) subunits or their "scaffold" proteins produce opposite effects on AMPAR surface delivery. Considering AMPARs have long been identified as suitable drug targets for central nervous system (CNS) disorders, targeting palmitoylation signaling to regulate AMPAR function emerges as a novel therapeutic strategy. However, until now, much less is known about the effect of palmitoylation‐deficient state on AMPAR function. Herein, we set out to determine the effect of global de‐palmitoylation on AMPAR surface expression and its function, using a special chemical tool, N‐(tert‐Butyl) hydroxylamine (NtBuHA). Methods: BS 3 protein cross‐linking, Western blot, immunoprecipitation, patch clamp, and biotin switch assay. Results: Bath application of NtBuHA (1.0 mM) reduced global palmitoylated proteins in the hippocampus of mice. Although NtBuHA (1.0 mM) did not affect the expression of ionotropic glutamate receptor subunits, it preferentially decreased the surface expression of AMPARs, not N ‐methyl‐d‐aspartate receptors (NMDARs). Notably, NtBuHA (1.0 mM) reduces AMPAR‐mediated excitatory postsynaptic currents (mEPSCs) in the hippocampus. This effect may be largely due to the de‐palmitoylation of postsynaptic density protein 95 (PSD95) and protein kinase A‐anchoring proteins, both of which stabilized AMPAR synaptic delivery. Furthermore, we found that changing PSD95 palmitoylation by NtBuHA altered the association of PSD95 with stargazin, which interacted directly with AMPARs, but not NMDARs. Conclusion: Our data suggest that the palmitoylation‐deficient state initiated by NtBuHA preferentially reduces AMPAR function, which may potentially be used for the treatment of CNS disorders, especially infantile neuronal ceroid lipofuscinosis (Batten disease).